Answer:
(4,0)
Explanation:
So we have the system of equations:
![y=-2x+8\\y=x-4](https://img.qammunity.org/2021/formulas/mathematics/college/75wduzqsw5xc9fmlab2fy3bameiquqzd0d.png)
To solve, we can use substitution.
Substitute the second equation into the first. So:
![x-4=-2x+8](https://img.qammunity.org/2021/formulas/mathematics/college/e2sfvd0xwforhz60hf3hqq2svnmxs8wy14.png)
Add 2x to both sides. The right cancels:
![3x-4=8](https://img.qammunity.org/2021/formulas/mathematics/college/hntsj6dzi3g6dhp6z792z32xkblunrvqs2.png)
Add 4 to both sides:
![3x=12](https://img.qammunity.org/2021/formulas/mathematics/middle-school/doasa9kf9mmn0883at1fbrl97mriajuen3.png)
Divide both sides by 3:
![x=4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/a1fs70p5exgs68ljexkqkiueya3liaz52t.png)
Now, let's substitute this back into the second equation to find y:
![y=x-4](https://img.qammunity.org/2021/formulas/mathematics/high-school/hrohsgs6etegyygb0ty9cqafdx9h2b52p8.png)
Substitute 4 for x:
![y=4-4](https://img.qammunity.org/2021/formulas/mathematics/college/szasnqrcbvafaholegby2u1ou3b1yttrdy.png)
Subtract:
![y=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/3bpgiogwa16ug3yokuqlgznnvo86fqgw4l.png)
So, our solution is (4,0).
And we're done!